Data Mining Identifies Differentially Expressed Circular RNAs in Skeletal Muscle of Thermally Challenged Turkey Poults - Reed, Kent M.; Mendoza, Kristelle M.; Abrahante, Juan E.; Velleman, Sandra G.; Strasburg, Gale M. (Frontiers in Physiology, 2021)
Precise regulation of gene expression is critical for normal muscle growth and development. Changes in gene expression patterns caused by external stressors such as temperature can have dramatic effects including altered cellular structure and function. Understanding the cellular mechanisms that underlie muscle growth and development and how these are altered by external stressors are crucial in maintaining and improving meat quality. This study investigated circular RNAs (circRNAs) as an emerging aspect of gene regulation. We used data mining to identify circRNAs and characterize their expression profiles within RNAseq data collected from thermally challenged turkey poults of the RBC2 and F-lines. From sequences of 28 paired-end libraries, 8924 unique circRNAs were predicted of which 1629 were common to all treatment groups. Expression analysis identified significant differentially expressed circRNAs (DECs) in comparisons between thermal treatments (41 DECs) and between genetic lines (117 DECs). No intersection was observed between the DECs and differentially expressed gene transcripts indicating that the DECs are not simply the result of expression changes in the parental genes. Comparative analyses based on the chicken microRNA (miRNA) database suggest potential interactions between turkey circRNAs and miRNAs. Additional studies are needed to reveal the functional significance of the predicted circRNAs and their role in muscle development in response to thermal challenge. The DECs identified in this study provide an important framework for future investigation.